2008
DOI: 10.1007/s10649-008-9140-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of teachers’ choice of examples in and for the mathematics classroom

Abstract: The main goal of the study reported in our paper is to characterize teachers' choice of examples in and for the mathematics classroom. Our data is based on 54 lesson observations of five different teachers. Altogether 15 groups of students were observed, three seventh grade, six eighth grade, and six ninth grade classes. The classes varied according to their level-seven classes of top level students and six classes of mixed-average and low level students. In addition, pre and post lesson interviews with the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
23

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 16 publications
1
38
0
23
Order By: Relevance
“…From the theoretical standpoint taken, we argue that which examples are chosen and how they are enacted together with students, are of decisive importance. Zodik and Zaslavsky's (2008) study indicates that teachers' choices of examples are seldom discussed. In a study of five in-service teachers' choices of examples, it was found that the teachers had never talked about their use of examples in pre-service training or with other colleagues in the school (Zodik and Zaslavsky 2008).…”
Section: Variation and Exemplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the theoretical standpoint taken, we argue that which examples are chosen and how they are enacted together with students, are of decisive importance. Zodik and Zaslavsky's (2008) study indicates that teachers' choices of examples are seldom discussed. In a study of five in-service teachers' choices of examples, it was found that the teachers had never talked about their use of examples in pre-service training or with other colleagues in the school (Zodik and Zaslavsky 2008).…”
Section: Variation and Exemplificationmentioning
confidence: 99%
“…Zodik and Zaslavsky's (2008) study indicates that teachers' choices of examples are seldom discussed. In a study of five in-service teachers' choices of examples, it was found that the teachers had never talked about their use of examples in pre-service training or with other colleagues in the school (Zodik and Zaslavsky 2008). In the following section, we give an empirical illustration of one teacher's teaching after he had worked with variation theory as a design principle for teaching.…”
Section: Variation and Exemplificationmentioning
confidence: 99%
“…Mesela, derslerimizde verdiğimiz karşıt örnekler, bir matematiksel yargının her durumda geçerli olmayabileceğini açıklarken; aynı zamanda "genellenebilirlik" göreviyle matematiksel kavramların teorik doğasına katkıda bulunur. Matematik eğitimi alanında teorik çatısını "örneklendirme" (exemplification) üzerine kuran çok sayıda araştırma ile karşılaşmak mümkündür (Rowland, 2008;Zodik ve Zaslavsky, 2008). Bu araştırmalarda "örnek" kavramı için birbiri ile örtüşen çok sayıda tanım yapılmıştır.…”
Section: Matematik Eğitiminde öRneklerin Rolüunclassified
“…Çünkü ders kitaplarındaki öğretim içeriklerinin öğrenciye ulaşması sürecinde en etkin rolü öğretmenler üstlenmektedir (Brousseau, 1986). Pek çok çalışmada, sınıfta kullanılan örneklerin tercihinde belirleyici olan bileşenin, öğretmen pratiği olduğuna dikkat çekilmiştir (Zodik ve Zaslavsky, 2008;Chick, 2009). Bu çalışma kapsamında öğretim elemanlarının örnek verme davranışları değerlendirileceğinden dolayı, 'matematik eğitiminde örnekler' temalı araştırmalar arasından, özellikle öğretmen pratiğini konu alan literatür paylaşılacaktır.…”
Section: Matematik Ders Kitaplarındaki öRneklerin Yapısıunclassified
See 1 more Smart Citation